Efficacy of Matrine, Rotenone, and Pyrethrin Against Red Imported Fire Ant Solenopsis invicta (Hymenoptera: Formicidae) and Their Impact on Aquatic Organisms. Issue 5 (20th September 2022) - Liang, Mingrong; Zhang, Senquan; Zheng, Xiaobin; Deng, Jiefu; Yang, Jiaqi; Liang, Yuling; Li, Zhiqiang; Yue, Xinlu; Lu, Yongyue; Xu, Yijuan; Wang, Lei
Abstract: Chemicals, including toxic bait and dusts, are the main means of controlling the red imported fire ant Solenopsis invicta (abbreviation 'RIFA'), which is a serious invasive pest. To identify environmentally friendly chemicals for controlling RIFA, we tested the toxicity and horizontal transfer of three botanical insecticides—matrine, rotenone, and pyrethrin—and their impact on aquatic organisms (i.e., three fish and one shrimp). The LD50 value of matrine, rotenone, and pyrethrin was 0.24, 50.929, and 13.590 ng/ant, respectively. Matrine, rotenone, and pyrethrin had effective horizontal transfer and caused significant secondary mortality. After exposure to donor workers, 90.75%, 90.75%, and 100% of recipient workers in the 0.025% matrine, 1.0% rotenone, and 0.3% pyrethrin dust treatments, respectively, died within 48 h. Furthermore, 0.025% matrine dust caused significant tertiary mortality (49.5%). Tertiary mortality caused by 1.0% rotenone and 0.3% pyrethrin dusts was very low, only 7.75% and 18.5%, respectively. In a field trial, the comprehensive mortality effect of 0.05% matrine, 1.50% rotenone, and 0.375% pyrethrin dust was 74.96%, 30.10%, and 29.27%, respectively, after 14 d of treatment. Matrine had low toxicity to the fish Hypophthalmichthys molitrix, and 37.5 mg/L pyrethrin had low toxicity to the fish Cirrhinus molitorella, H. molitrix, and Oreochromis niloticus . However, rotenone was highly toxic to all three fish. The shrimp Neocaridina denticulate was not sensitive to matrine, rotenone, or pyrethrin. Matrine dust has highly effective horizontal transfer, and 0.05% matrine dust has great potential for managing RIFA in organic farms, aquaculture farms of H. molitrix, and water resource regions.